Amiodarone-Induced Thyrotoxicosis: Differential Diagnosis Using 99mTc-SestaMIBI and Target-to-Background Ratio (TBR). (September 2018) - Censi, Simona; Bodanza, Valentina; Manso, Jacopo; Gusella, Sara; Watutantrige-Fernando, Sara; Cavedon, Elisabetta; Barollo, Susi; Bertazza, Loris; Cecchin, Diego; Mian, Caterina
Abstract : Purpose of the Report: Distinguishing between amiodarone-induced thyrotoxicosis (AIT) caused by excessive hormone synthesis (AIT-1) or by a destructive process (AIT-2) has important therapeutic implications, but is still difficult and debated. 99m Tc-sestaMIBI thyroid scintigraphy (99m-STS) has been proposed as a tool for classifying the two forms. Material and Methods: 30 AIT patients (11 females and 19 males) who underwent 99m-STS were retrospectively assessed for the present study. For each patient, a target-to-background ratio (TBR) was obtained on planar images. The TBR was then correlated with the qualitative assessment of the scans and the final clinical diagnosis. Results: Considering clinical response to treatment as the gold standard for differential diagnosis, 14 cases of AIT-1, 12 of AIT-2, and 4 mixed forms were identified. 99m-STS was able to qualitatively identify all the mixed forms, while 1/14 AIT-1 and 6/12 AIT-2 cases were misdiagnosed as mixed forms. When the quantitative index (the TBR) was compared with the final clinical diagnosis, ROC curve analysis enabled us to identify an IBR of 0.482 during 99m-STS as a cut-off capable of discriminating between AIT-1 and AIT-2, with 100% specificity and 91.7% sensitivity ( P < 0.0001, area under the curve: 0.982). Conclusions: Taking the TBR into consideration, 99m-STS proved a very useful tool for distinguishing AIT-1 from AIT-2, and thus offering patients appropriate treatment as of their diagnosis. This approach can avoid pointless and potentially dangerous combined overtreatments, and may speed up the return to normal thyroid function, which is crucial in AIT patients suffering from heart disease.